ANALISIS KEPUASAN PENGGUNA TERHADAP LAYANAN APLIKASI GOFOOD MENGGUNAKAN MOBILE SERVICE QUALITY DENGAN METODE CSI - ., Agustiawan; Sudirman; Marlina (STMIK KHARISMA Makassar, 2024)
Gofood is one of the applications in Gojek, the application is used by customers to find and order culinary. When the author conducted research on the gofood application, it turned out that some reviewed it well, and some reviewed it badly. This study aims to analyze the level of satisfaction of gofood application users with the Mobile Service Quality method and the Customer satisfaction index (CSI) which is a method that uses an index to calculate the level of consumer satisfaction in a user satisfaction survey. Respondent data from questionnaires that have been distributed via google form and have been filled in by Gofood application users as many as 70 respondents. Based on the results of research that has been conducted on the Gofood application using the Customer Satisfaction Index (CSI) method, it can be concluded that the research results from the CSI value obtained of 85.42% is very satisfied, because the results of the CSI value are obtained after calculating the CSI method through four stages, the first stage determines the mean importance score (MIS) and mean satisfaction score (MSS), the second stage weight factor (WF), the third stage weight score (WS), and the last stage determines the Customer Satisfaction Index (CSI). So it can be concluded that most users of the Gofood application at STMIK Kharisma Makassar are very satisfied with the services in the Gofood application.